NARASI TENTANG AUTISM DI FACEBOOK (Studi Autoetnografi pada Status K.W) - Kusumastuti, Frida; Leonardo, Jeanne; Widiatmojo, Radityo (Master of Communication Science Program, Universitas Diponegoro, 2019)
The narrative of a mother who is directly involved in living with a child with an autistic child's lifetime is worth noting because it can complement the narrative of the Professionals (doctors, psychiatrists, psychologists, educators). Especially if the narrative is done openly on social media such as Facebook. Social Media gives the opportunity of public voices that were originally being repossessed by large narratives. Thus the purpose of this research is to interpret the narrative of the subject about autism based on daily experience (everyday life). Narrative is the way someone tells his experience. The narrative about Autism, commonly referred to as